Carotid Artery Stenting–Historical Context, Trends, and Innovations - Spacek, Miloslav; Veselka, Josef (International Journal of Angiology, 2015)
Surgical carotid endarterectomy (CEA) has been proven effective in both primary and secondary stroke prevention and, until recently, has been considered the standard treatment approach for patients with severe carotid artery disease. Because of its technical limitations and less favorable outcomes, carotid artery stenting (CAS) has been offered preferably to patients considered to be too comorbid to undergo surgical treatment. However, CAS has evolved over time into a reliable method and is currently considered an alternative to CEA. The aim of this review was to discuss the historical aspects, trends, and innovations in CAS.
Keywords: carotid stenting; carotid endarterectomy; emboli protection device; carotid stents